The Role of E-Portfolio Assessment in Students’ Reflection for Enhancing EFL Learners’ Outcome - Prapti Wardani; Nunung Nurjati; Nukmatus Syahria (Jurnal Pendidikan Indonesia, 2025)
This research explores the role of e-portfolios in enhancing reflective practice and language proficiency among English as a Foreign Language (EFL) learners. E-portfolios provide a structured platform for students to document learning artifacts, engage in self-reflection, and monitor progress, fostering deeper insights into their language development. The research aims to evaluate the effectiveness of e-portfolios in improving learning outcomes and identify challenges in their implementation. Using a mixed-methods approach, data were collected from 161 EFL students and teachers in East Java, Indonesia, through online questionnaires and Likert-scale assessments. Findings reveal that 74.6% of students had positive experiences with e-portfolios, with 70% noting improved language competency through regular reflection. Teachers (85%) viewed e-portfolios as valuable for tracking progress and engagement, though some lacked training. Key challenges included time management (60%) and varying student confidence levels in reflection (42.9%). Best practices for effective implementation include teacher professional development, curriculum integration, peer collaboration, and structured feedback. The study highlights e-portfolios' potential to transform EFL education but notes limitations due to its regional sample. Implications suggest broader adoption of e-portfolios, supported by training and policy frameworks, to enhance reflective learning and language proficiency in diverse EFL contexts.